Counseling students to improve fire safety knowledge and preparedness - Simanjuntak, Mafe Robbi; Dameria, Dameria; Situngkir, Luwis; Sihombing, Tabita Ronauli; Ginting, Astriani Natalia Br; Sianipar, Milka Rositi (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
This research investigates the effectiveness of counseling methods, incorporating seminar models and PowerPoint presentations, in enhancing students’ knowledge and preparedness for fire emergency response at Universitas Prima Indonesia. A quantitative approach with a quasi-experimental, one-group pretest-posttest design was employed, involving 78 students from the Public Health Bachelor Program. The intervention comprised four counseling sessions covering basic fire knowledge, preparedness steps, emergency actions, and the use of firefighting equipment. Data was collected through questionnaires administered before and after the intervention, assessing students' knowledge of fire extinguishers, hydrants, fire alarms, assembly points, emergency exits, and emergency stairs. The results indicated a significant positive impact, with post-test scores for both knowledge and preparedness substantially higher than pre-test scores (p < 0.001). Before the intervention, only 25.6% of participants demonstrated good knowledge, while after the intervention, 97.4% achieved this level. Similarly, preparedness levels significantly increased, with 97.4% of participants feeling ready after the intervention compared to only 19.2% before. The study underscores the effectiveness of the implemented counseling methods and supports the recommendation for continuous fire safety education to ensure sustained preparedness.